Kolom Kosong Legal Review of Empty Column Volunteer Activities in the 2024 Simultaneous Regional Head Elections in Pangkalpinang City: Legal Review of Empty Column Volunteer Activities in the 2024 Simultaneous Regional Head Elections in Pangkalpinang City - Jazzkyanda (TERAJU: Jurnal Syariah dan Hukum, 2026)
The single candidate pair in the 2024 Simultaneous Regional Head Elections in Pangkalpinang City presents a new dynamic in the practice of electoral democracy in Indonesia. Backed by 16 political parties, the single candidate pair, Maulana Aklil and Masagus Hakim, face the Empty Column as an alternative choice for voters in Pangkalpinang City. The emergence of ‘Empty Column’ volunteers demonstrates a form of community resistance against the dominance of political parties that stifles healthy political competition. However, to date, there has been no regulation explicitly governing the campaign activities or outreach carried out by ‘Empty Column’ volunteers. This situation creates a legal vacuum that poses obstacles for the General Elections Commission (KPU) and the Elections Supervisory Agency (Bawaslu), as election organisers, in facilitating and closely supervising the activities of the Empty Column volunteers. This study aims to analyse the legal status and activities of the Empty Column volunteers within the context of Indonesian election law. The research method employed is normative legal research, utilising a statutory and conceptual approach. The findings indicate that, legally, the Empty Column volunteers cannot be classified as election participants as defined in Law No. 10 of 2016; however, their activities cannot be disregarded as they influence public political participation. Consequently, regulatory clarity is required to ensure the activities of the Empty Column volunteers are appropriately situated within Indonesia’s electoral legal framework.